Authenticity and the Stimulated Self: Neurosurgery for Anorexia Nervosa - Savulescu, J; Maslen, H; Pugh, J (Nature, 2015)
Mueller et al. address a range of ethical considerations associated with neurosurgical interventions for the treatment of Anorexia Nervosa (AN), arguing for several protective measures to safeguard clinical research and practice. This is an important article, which provides a thorough review of current neurosurgical research and presents key insights into challenges associated with compromised decision-making capacities in the context of AN and the early average age of onset. We have argued elsewhere that further considerations relate to the ways in which the potential mechanisms deep brain stimulation (DBS) affect the patient’s desires, cognitive control and emotions, with distinct consequences for autonomy (these points are developed in Maslen et al. (under review)). In addition, as we will outline here, ethical analysis of DBS and ablative surgery for AN should explicitly address the authenticity of patients’ desires and experiences. Mueller et al. do consider the related issues of personality and identity. First, they suggest that, since it is not possible to adequately inform patients about the effects that psychiatric neurosurgery might have on their personality or identity, it might not be possible for patients to provide sufficiently informed consent to the procedure (17). Second, they point out that DBS might alter personality or identity when considering coercive interventions in adolescents, concluding that this constitutes one of two jointly-decisive reasons not to perform neurosurgery against the adolescent’s will. In this context, they hint at authenticity when they quote Charland’s claim that ‘many AN patients oscillate ambiguously between the view that anorexia is a part of their true self, and that it has completely taken over their self’(x). However, it is somewhat striking that they neither use nor examine the concept of authenticity. We describe the way this concept features in discussions of AN, and suggest that a deeper understanding of authenticity reveals further ethical problems that Mueller et al. do not consider. In this commentary, we focus on DBS as the neurosurgical intervention about which there is the most optimism in the context of AN treatment. We note that ablative surgery will raise other profound issues because they will not be reversible.